Selling luxury : connect with affluent customers, create unique experiences through impeccable service, and close the sale - Lent, Robin (Wiley, 2009)
Praise for Selling Luxury "Geneviève and Robin have brought together their talents to create a book that gives all Sales Ambassadors the fundamentals in selling and building customer loyalty."--Hamida Belkadi, CEO, De Beers Diamond Jewellers, USA "Selling Luxury is filled with ways of exceeding each client's expectations through offering a service that surprises and delights." - Aaron Simpson, Group Executive Chairman, Quintessentiall What does it take to sell high-end luxury creations to the richest clients in the world? In Selling Luxury, Robin Lent and Genevieve Tour, with thirty years of combined experience, share their savoir-faire. You'll also pick up tips from multi-million dollar luxury sales professionals who will help you understand the complexities of the universe of luxury. Selling Luxury will show you how a salesperson can acquire Sales Ambassador status by offering the impeccable service associated with the world's most prestigious brands.